2019
DOI: 10.1021/acs.energyfuels.8b04135
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Full-Sized Pore Structure of Coal-Bearing Shales and Its Effect on Shale Gas Content

Abstract: The characterization of the pore structure and shale gas content provides useful information for shale gas reservoir assessment and evaluation and guides the exploration and development of shale gas. Fresh core samples obtained from three different basin formations in China were analyzed by field-emission scanning electron microscopy, low-pressure CO 2 and N 2 gas adsorption−desorption, high-pressure mercury intrusion, and methane adsorption experiments to clarify the pore structure characteristics of coal-bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 57 publications
(187 reference statements)
0
30
0
Order By: Relevance
“…The fractal dimension can be used to quantitatively describe the irregularity of a set. Previous studies have shown that the pore structure of coal rock has obvious fractal characteristics 39 . To investigate the scale characteristics of the pore‐fracture structure in the coal samples, the MIP results of the water‐injected samples were analyzed based on fractal theory.…”
Section: Resultsmentioning
confidence: 99%
“…The fractal dimension can be used to quantitatively describe the irregularity of a set. Previous studies have shown that the pore structure of coal rock has obvious fractal characteristics 39 . To investigate the scale characteristics of the pore‐fracture structure in the coal samples, the MIP results of the water‐injected samples were analyzed based on fractal theory.…”
Section: Resultsmentioning
confidence: 99%
“…The pore structure of shales has strong heterogeneity, such as the PSD in the shale ranges from nanometer to micrometer scales; macropores, mesopores, and micropores have different contributions to the PV and SSA, respectively (Zhang J. et al, 2017;Zhang J. et al, 2019). The pore is the main place to adsorb and gather gas.…”
Section: Characterization Of the Full-sized Pore Structurementioning
confidence: 99%
“…The increased energy and environmental demands promoted rapid development of the shale gas industry (Sun et al, 2017;Zhang J. et al, 2019;Xie et al, 2021). Unlike conventional reservoirs, shale gas is mainly stored in adsorbed and free states in complex pore systems (Ding et al, 2013;Wang et al, 2015;Chen et al, 2016;Sun et al, 2021;Tang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…), ray methods ,, (such as small-angle X-ray scattering (SAXS), (super) small-angle neutron scattering, etc. ), and fluid injection methods (such as MICP, LT-NA/D, and carbon dioxide gas adsorption (LPA), low-field nuclear magnetic resonance (NMR), etc.). With regard to shale gas extraction, only connected pores will affect the migration and diffusion of shale gas, thereby controlling shale gas production to a certain extent.…”
Section: Introductionmentioning
confidence: 99%